Penglibatan komuniti dalam pembangunan Gua Harimau sebagai tapak pelancongan arkeologi - Sarkomi, Aufa Syahrizal (2023)
Tourism was a thriving industry after the Second World War (1941-1945). The exciting development of the tourism industry has prompted most countries to develop tourism seriously because of its ability to contribute to economic growth. To ensure that the tourism industry is able to provide returns and benefits to all parties at all times, a comprehensive and integrated planning needs to be done. Good planning is to consider all aspects involved before implementing development. Therefore, it is necessary to build good cooperation between the community and the government as a driver of development and direct community involvement in development programs, so that it can have a positive impact on the condition and standard of living of the community itself. The various results of previous studies have found is a mixture of findings and differences of opinion on community involvement in tourism development, including the development of the Harimau Cave site. Therefore, this matter needs to be studied and explored, especially on the views of the community and the extent of community involvement in Padang Bindu village on the development of the Harimau Cave site as an archaeological tourism destination. This research applies a qualitative approach in the data collection process by using questionnaires, interviews with local communities and the government. The data obtained were analyzed using thematic analysis methods. The results of the study found that the Tiger Cave area has the potential to be developed as an archaeological tourist attraction. In general, the local community gives strong support if the existence of the Tiger Cave site area becomes an archaeological tourist attraction although the community involvement in planning and decision making is still limited and sometimes neglected.